Exploring the role of brand image and influencer marketing in a monopolistic competitive market - Andi Mappatompo; Suhermin Suhermin; Martaleni Martaleni; Fitria Ariyani (Faculty of Economics and Business, University of Muhammadiyah Malang, 2025)
This study aims to analyze the influence of influencer marketing on purchasing intention with brand image as a mediating variable in a monopolistic competitive market. Using the Robust Least Square method, this study tested data from 100 respondents selected through purposive sampling: consumers who actively use body care products daily. The study results indicate that influencer marketing significantly influences building brand image, which becomes the main factor in increasing purchasing intention. However, no direct effect was found between influencer marketing and purchasing intention, thus emphasizing the role of brand image as a link between the two. In a monopolistic market, where competition focuses on non-price differentiation, brand image has proven to be a strategic asset that strengthens brand position. Influencer marketing helps create emotional narratives, credibility through endorsements, and personal relationships with audiences, all of which enhance brand image. Overall, this study emphasizes the importance of brand image management as the core of a digital marketing strategy. With a strong brand image, companies can increase purchasing intention, create consumer loyalty, expand product portfolios, and increase competitiveness in a dynamic industry